Staff perspectives on the feeding practices used in holiday clubs to promote healthy eating in disadvantaged communities. (17th February 2022) - Bayes, Natasha; Mason, Carolynne; Holley, Clare E.
Abstract: An increasing number of holiday clubs provide free meals to alleviate children's hunger during the school holidays. Holiday clubs are well‐placed to promote healthy eating among children from disadvantaged communities who may be at risk of experiencing food insecurity, but currently little is known about the feeding practices used by staff and whether these are conducive to maximising opportunities to promote healthy eating. Unlike previous research which has predominantly studied feeding practices in parent‐child dyads and childcare settings, this qualitative study explored staff perspectives on the feeding practices they use to promote healthy eating within nine UK holiday clubs working with children from disadvantaged communities. Nine individual interviews and four focus groups were completed with 27 holiday club staff during the 2019 summer holidays. Thematic analysis revealed seven feeding practice themes, including teaching about nutrition; encouraging balance and variety; modelling; involvement; non‐food rewards; restriction; and reoffering foods. The results revealed that some staff implement various positive feeding practices which align with the existing evidence‐base of feeding practices in other contexts, which is a promising finding given the current lack of information and guidance from which to draw on. However, staff also sometimes reported using maladaptive feeding practices, including overt restriction and punishment. These results emphasise the need for guidance on effective ways to implement feeding practices with children in holiday clubs. Indeed, staff demonstrated their receptivity to engaging with training resources to maximise their opportunities to promote healthy eating behaviours among children.